Empirische Befunde der Interessenforschung der Fächer Biologie, Chemie und Physik im Primar- und Sekundarbereich seit 2012 – Ein systematisches Review - Habig, Sebastian; Großmann, Nadine; Schmid, Andrea M.; van Vorst, Helena; Fechner, Sabine; Wilde, Matthias (Interesse revisited)

Interessenförderung im Physik- und Chemieunterricht – Eine Bestandsaufnahme - Zöchling, Sarah; Pletschacher, Laura; Maurer, Christian; Berger, Roland; Lindmaier, Kerstin; Fechner, Sabine; Wodzinski, Rita (Interesse revisited)

Molecular Orientation‐Dependent Photonic Spin–Orbit Coupling in Organic Microcavities Filled with 2D Polymorphic Crystals - Ji, Ying; Ma, Xuekai; Huang, Han; Deng, Yibo; Wang, Pingyang; Long, Teng; Li, Yuan; Zhao, Ruiyang; Li, Yunfei; An, Cunbin; Schumacher, Stefan; Gu, Chunling; et al. (Laser & Photonics Reviews)
ABSTRACT Effective manipulation of photonic spin–orbit coupling (SOC) in microcavities is of fundamental importance within topological photonics and applications. Anisotropic organic single‐crystalline materials can induce abundant SOC phenomenon due to their flexible tunability of molecular geometries, however, the intrinsic relationship between molecular geometries/orientations in 3D space and photonic SOC is lacking. In this study, we design two kinds of 2D organic polymorphs for the construction of organic microcavities to investigate the structure‐performance relationships. In two polymorphic microcavities, two distinctive photonic SOC phenomena are observed regardless of the in‐plane anisotropy of organic polymorphs. Theoretical analysis indicates that the photonic SOC strength is strongly influenced by the synergies between the crystal anisotropy and the tilted collective molecular transition dipole moment. Our results uncover the correlation mechanism between the structure of molecules and photonic SOC and open an avenue to engineer complex photonic SOC by use of organic microstructures towards the development of diverse integrated photonic devices.

Tuning polariton vortices in an asymmetric ring potential - Ai, Qiang; Ma, Xuekai; Barkhausen, Franziska; Zhai, Xiaokun; Xing, Chunzi; Yang, Xinmiao; Wang, Peilin; Liu, Tianyu; Zhang, Yong; Gu, Yazhou; Li, Peigang; Li, Zhitong; et al. (Applied Physics Letters)
Exciton polariton condensates are macroscopic coherent states in which topological excitations can be observed. In this work, we observe the excitation of the vortices and realize tuning the topological charge by manipulating the pumping configurations. Using a digital micromirror device, we constructed an annular pumping pattern where the inner and outer rings can be easily tuned. Both the number and the topological charge of the vortices can be changed by slightly tuning the inner ring position against the outer ring. The experimental results can be reproduced in theory by the Gross–Pitaevskii equation. Our work offers to generate and manipulate vortices in exciton polariton condensates using a straightforward optical method.

Higher-order dark solitons and control dynamics in microcavity polariton condensates - Sun, Jinming; Chen, Manna; Schumacher, Stefan; Hu, Wei; Ma, Xuekai (Physical Review B)

In Situ PM‐IRRAS and XPS Analysis of Nitrogen Plasma Surface Modification of Polylactide Thin Films - Gołębiowska, Sandra; Voigt, Markus; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Surface and Interface Analysis)
ABSTRACT Spin‐coated polylactide (PLA) thin films were exposed to nitrogen plasma for varying time intervals. The progressive etching of the PLA film in direct contact with the nitrogen plasma was monitored in situ using polarization modulated infrared reflection absorption spectroscopy (PM‐IRRAS). No appreciative changes in composition were seen with PM‐IRRAS, indicating that the etching did not significantly affect the bulk composition. Atomic force microscopy characterization of the plasma‐etched films showed that the PLA films are homogeneously etched. Subsequent ex situ XPS analysis of the treated surface revealed the presence of C‐N bonds in the surface‐near region that could be associated with amino and/or amide surface species. PLA films were also alternatively exposed to nitrogen ion beams produced by an electron‐cyclotron‐resonance (ECR) plasma source and were investigated in vacuo by XPS. This treatment revealed the partial substitution of surface oxygen species by nitrogen, resulting in a similar surface modification as in the plasma case. The comparison of XPS data and water contact angle studies suggest that the activated surfaces show a reorientation of macromolecular fragments in the surface‐near region depending on the polarity of the phase with which they are in contact. Under ultra‐high vacuum (UHV) conditions, the surface tends to lower its surface energy, while in contact with the aqueous phase, subsurface polar groups orientate outwards, which enables the formation of hydrogen bonds.

Evaluation of anti-adhesive and corrosion protection properties of TiAlSiN-magnetron-sputtered films for applications in polymer processing - Theile-Rasche, Chantal; Wang, Fuzeng; Prüßner, Tim; Huck, Marten; Steinrück, Hans-Georg; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Thin Solid Films)

DNA origami adsorption at single-crystalline TiO2 surfaces - Xu, Xiaodan; Gołębiowska, Sandra; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido; Keller, Adrian (RSC Applied Interfaces)
DNA origami adsorption at single-crystalline TiO 2 surfaces is investigated at different Mg 2+ concentrations. For TiO 2 (001), DNA origami adsorption is stronger at 5 mM than at 10 mM Mg 2+ , whereas the opposite is observed for TiO 2 (110) and TiO 2 (111).

High-fidelity quantum entanglement distribution in metropolitan fiber networks with co-propagating classical traffic - Sena, Matheus; Flament, Mael; Andrewski, Shane; Caltzidis, Ioannis; Bigagli, Niccolò; Rieser, Thomas; Bello Portmann, Gabriel; Sekelsky, Rourke; Braun, Ralf-Peter; Craddock, Alexander N.; Schulz, Maximilian; Jöns, Klaus; et al. (Journal of Optical Communications and Networking)
The Quantum Internet, a network of quantum-enabled infrastructure, represents the next frontier in telecommunications, promising capabilities that cannot be attained by classical counterparts. A crucial step in realizing such large-scale quantum networks is the integration of entanglement distribution within existing telecommunication infrastructure. Here, we demonstrate a real-world scalable quantum networking testbed deployed within Deutsche Telekom’s metropolitan fibers in Berlin. Using commercially available quantum devices and standard add-drop multiplexing hardware, we distributed polarization-entangled photon pairs over dynamically selectable looped fiber paths ranging from 10 m to 60 km and showed entanglement distribution over up to approximately 100 km. Quantum signals, transmitted at 1324 nm (O-band), coexist with conventional bidirectional C-band traffic without dedicated fibers or infrastructure changes. Active stabilization of the polarization enables robust long-term performance, achieving entanglement Bell-state fidelity bounds between 85% and 99% and Clauser–Horne–Shimony–Holt parameter S -values between 2.36 and 2.74 during continuous multiday operation. By achieving a high-fidelity entanglement distribution with less than 1.5% downtime, we confirm the feasibility of hybrid quantum-classical networks under real-world conditions at the metropolitan scale. These results establish deployment benchmarks and provide a practical roadmap for telecom operators to integrate quantum capabilities.

Effectiveness of regular oat β-glucan–enriched bread compared with whole-grain wheat bread on long-term glycemic control in adults at risk of type 2 diabetes: a randomized controlled trial - Hjorth, Therese; Schadow, Alena Marie; Revheim, Ingrid; Spielau, Ulrike; Meyer, Klara; Rieder, Anne; Varela, Paula; Ballance, Simon; Koerner, Antje; Landberg, Rikard; Buyken, Anette; Dierkes, Jutta; et al. (The American Journal of Clinical Nutrition)

Wave packet dynamics in parabolic optical lattices: From Bloch oscillations to long-range dynamical tunneling - Ali, Usman; Holthaus, Martin; Meier, Torsten (Physical Review Research)
We investigate the dynamics of wave packets in a parabolic optical lattice formed by combining an optical lattice with a global parabolic trap. Our study examines the phase space representation of the system's eigenstates by comparing them to the classical phase space of a pendulum, to which the system effectively maps. The analysis reveals that quantum states can exhibit mixed dynamics by straddling the separatrix. A key finding is that the dynamics around the separatrix enables the controlled creation of highly nonclassical states, distinguishing them from the classical oscillatory or rotational dynamics of the pendulum. By considering a finite momentum of the initial wave packet, we demonstrate various dynamical regimes. Furthermore, a slight energy mismatch between nearly degenerate states localized at opposite turning points of the trap potential results in controlled long-range dynamical tunneling. These results can be interpreted as quantum beating between a clockwise rotating and a counterclockwise rotating pendulum.

Spectral and temporal properties of type-II parametric down-conversion: The impact of losses during state generation - Kopylov, Denis A.; Stefszky, Michael; Meier, Torsten; Silberhorn, Christine; Sharapova, Polina R. (Physical Review Research)
In this paper, we theoretically study the spectral and temporal properties of pulsed spontaneous parametric down-conversion (SPDC) generated in lossy waveguides. Our theoretical approach is based on the formalism of Gaussian states and the Langevin equation, which is elaborated for weak parametric down-conversion and photon-number-unresolved click detection. Using the example of frequency-degenerate type-II SPDC generated under the pump-idler group-velocity-matching condition, we show how the joint-spectral intensity, mode structure, normalized second-order correlation function, and Hong-Ou-Mandel interference pattern depend on internal losses of the SPDC process. We found that the joint-spectral intensity is almost insensitive to internal losses, while the second-order correlation function shows a strong dependence on them, being different for the signal and idler beams in the presence of internal losses. Based on the sensitivity of the normalized second-order correlation function, we show how its measurement can be used to experimentally determine internal losses.

Accelerating the analysis of optical quantum systems using the Koopman operator - Hunstig, Anna; Peitz, Sebastian; Rose, Hendrik; Meier, Torsten (2024 IEEE 63rd Conference on Decision and Control (CDC))

KI-Einsatz durch Lernende im Erkenntnisgewinnungsprozess - ein Review - Fox, Marvin Lee; Peeters, Hendrik; Fechner, Sabine (GDCP Jahrestagung)
Keywords: Artificial intelligence; education; chemistry

Phosphonic acid adsorption on α-Bi2O3 surfaces - Bocchini, Adriana; Kollmann, S.; Gerstmann, Uwe; Schmidt, Wolf Gero; Grundmeier, Guido (Surface Science)

Finite-size and relativistic effects onto hyperfine interaction of muonic hydrogen - Franzke, Katharina L.; Schmidt, Wolf Gero; Gerstmann, Uwe (Journal of Physics: Conference Series)
Abstract Muonic hydrogen is an exotic atom where a muon instead of an electron is bound to a proton. The comparably high mass of the muon (≈ 207 · m e ) has two important effects, (i) the reduced mass of the system becomes more important, and (ii) the muon is localized much closer to the nucleus. Thus, muonic hydrogen is not only excellently suitable for evaluating highly precise quantum electrodynamic (QED) calculations, but may also be used for assessing new approaches including finite nuclear size (FNS) effects to evaluate the proton structure and improve calculation schemes for the hyperfine splittings of many-particle systems, as e.g. to be implemented in density functional theory (DFT) software packages. Here, starting from Dirac’s equation we calculate the relativistic hyperfine splitting of the ground state and several excited states of muonic hydrogen analytically for different charge and magnetization models. The FNS related hyperfine shifts are compared with the differences between QED calculations and experimental measurements. This comparison also allows to unravel the role of the reduced mass, which is on one hand crucial in case of muonic atoms, but on the other hand is by no means well defined in relativistic quantum mechanics.

Dynamic and Reversible Plasmonic Nanogaps From Isolated Dimer Nanoparticles via Self-Assembly - Devaraj, Vasanthan; Ruiz Alvarado, Isaac Azahel; Lee, Jongmin; Oh, Jin-Woo; Gerstmann, Uwe; Schmidt, Wolf Gero; Zentgraf, Thomas (2025 Conference on Lasers and Electro-Optics Europe & European Quantum Electronics Conference (CLEO/Europe-EQEC))

Efficient n‐Doping of Organic Semiconductors via a Broadly Applicable Nucleophilic‐Attack Mechanism - Wei, Huan; Wu, Tong; Dong, Chuanding; Chen, Chen; Gong, Zhenqi; Xia, Jiangnan; Peng, Chengyuan; Ding, Jiaqi; Zhang, Yu; Shi, Wenpei; Schumacher, Stefan; Zhang, Xue; et al. (Advanced Science)
Abstract The development of efficient and broadly applicable n‐doping strategies for organic semiconductors (OSCs) is crucial for advancing the performance of various organic electronic devices. Here, a novel nucleophilic‐attack n‐doping mechanism is unveiled that achieves exceptionally high conductivity in doped OSC films and demonstrates broad applicability across OSCs. The remarkable efficacy of n‐Butyl lithium (n‐BuLi) is highlighted in n‐doping C 60 and PC 61 BM, achieving a conductivity of 1.27 S cm −1 and 2.57 S cm −1 , respectively, which are among the highest reported values for these materials. The investigation reveals that the n‐BuLi anion interacts with electron‐deficient units in OSCs, generating a carbanion that facilitates efficient electron transfer for n‐doping. This mechanism is further validated across diverse fullerenes, polymeric, and small molecule OSCs, and is extendable to other high‐performance dopants such as tert‐Butyllithium (tert‐BuLi) and sodium ethoxide (NaOEt). Device studies show that n‐BuLi‐doped C 60 enables substantially improved diode rectification, attributed to greater junction built‐in potential. These findings establish a unified chemical‐bonding‐based n‐doping paradigm, complementing existing electrophilic‐attack p‐doping concepts, and pave the way for achieving efficient doping of OSCs for advanced organic electronic applications.

Sensitivity and Topology of Exceptional Rings in Nonlinear Non-Hermitian Planar Optical Microcavities - Wingenbach, Jan; Ares Santos, Laura; Ma, Xuekai; Sperling, Jan; Schumacher, Stefan (Arxiv)
Non-Hermitian systems hosting exceptional points (EPs) exhibit enhanced sensitivity and unconventional mode dynamics. Going beyond isolated EPs, here we report on the existence of exceptional rings (ERs) in planar optical resonators with specific form of circular dichroism and TE-TM splitting. Such exceptional rings possess intriguing topologies as discussed earlier for condensed matter systems, but they remain virtually unexplored in presence of nonlinearity, for which our photonic platform is ideal. We find that when Kerr-type nonlinearity (or saturable gain) is introduced, the linear ER splits into two concentric ERs, with the larger-radius ring being a ring of third-order EPs. Transitioning from linear to nonlinear regime, we present a rigorous analysis of spectral topology and report enhanced and adjustable perturbation response in the nonlinear regime. Whereas certain features are specific to our system, the results on non-Hermitian spectral topology and nonlinearity-enhanced perturbation response are generic and equally relevant to a broad class of other nonlinear non-Hermitian systems, providing a universal framework for engineering ERs and EPs in nonlinear non-Hermitian systems.

Quantifying Spin Defect Density in hBN via Raman and Photoluminescence Analysis - Patra, Atanu; Konrad, Paul; Sperlich, Andreas; Biktagirov, Timur; Schmidt, Wolf Gero; Spencer, Lesley; Aharonovich, Igor; Höfling, Sven; Dyakonov, Vladimir (Advanced Functional Materials)
Abstract Negatively charged boron vacancies () in hexagonal boron nitride (hBN) are emerging as promising solid‐state spin qubits due to their optical accessibility, structural simplicity, and compatibility with photonic platforms. However, quantifying the density of such defects in thin hBN flakes has remained elusive, limiting progress in device integration and reproducibility. Here, an all‐optical method is presented to quantify defect density in hBN by correlating Raman and photoluminescence (PL) signatures with irradiation fluence. Two defect‐induced Raman modes, D1 and D2, are identified and assigned them to vibrational modes of using polarization‐resolved Raman measurements and density functional theory (DFT) calculations. By adapting a numerical model originally developed for graphene, an empirical relationship linking Raman (D1, E 2g ) and PL intensities is established to absolute defect densities. This method is universally applicable across various irradiation types and uniquely suited for thin flakes, where conventional techniques fail. The approach enables accurate, direct, and non‐destructive quantification of spin defect densities down to 10 15 defects/cm 3 , offering a powerful tool for optimizing and benchmarking hBN for quantum optical applications.